Analysis of Internal Migration in Brooke’s Point, Palawan: Implications for Policy Formulation (2025) - Bruno, Marcus Miguel A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the internal migration dynamics in Brooke’s Point, Palawan, with particular emphasis on the socio-economic demographic profile of in-migrants, the key aspects influencing migration, and its economic, social, and environmental implications for local development.Employing a descriptive-empirical survey design, data were gathered from 381 respondents across eight barangays with significant migrant populations.Quantitative data were analyzed using descriptive and inferential statistics, including Pearson’s r and Chi-square tests, to determine relationships between socio-economic variables and migration patterns.Findings reveal that internal migration in Brooke’s Point is primarily economically driven, dominated by working-age, married, and male individuals seeking better livelihood opportunities.The municipality’s role as a regional agro-industrial hub has made it a major destination for migrants from Luzon and the Visayas.Most migrants are semi-skilled and engaged in informal or self-employed work, reflecting both the opportunities and vulnerabilities of migration.The study affirms E. Lee’s Push-Pull Theory, with lack of jobs as the strongest push factor and employment availability as the main pull factor, while De Haas’ Migration Transition Theory explains the shift from survival-driven to opportunity-driven migration. Migration has generated largely positive effects stimulating business growth, expanding markets, and fostering cultural diversity.However,challenges persist, including underemployment, social integration gaps, and environmental strain from unregulated settlement expansion.To address these, the study recommends integrating the Balik Probinsya, Bagong Pag-asa (BP2) framework in local governance, strengthening skills training and livelihood programs, promoting social cohesion, and enforcing sustainable land-use policies.Overall, internal migration in Brooke’s Point emerges as both a transformative and strategic force for inclusive and sustainable rural development.